Recursive mean-separate histogram equalisation method. - Ramli, Abdul Rahman; Chen, Soong Der (2004)

(untitled)
The present invention relates to recursive mean-separate histogram method to enhance the contrast of an image and to recursively mean separate the input image so that the output image mean brightness will coverage to the input image mean. The process is that an input image is divided into a predetermine number of sub-image and then calculate the cumulative density. Next, the sub-image is histogram equalised independently. This invention provide a scalable brightness preservation, and more importantly the method is very useful in consumer electronic products.